Legal Responsibility for Maladministration in the Issuance of Mining Business Permits - Aullia Vivi Yulianingrum; Insan Tajali Nur; Suryaningsi Suryaningsi; Aldi Pebrian (CV. RADJA PUBLIKA, 2026)
This study analyzes the forms of maladministration in the issuance of Mining Business Permits and examines the legal responsibilities that may be imposed on officials or government institutions involved in such practices. The study employed a normative legal method, drawing on statutory, conceptual, and case approaches. The legal materials consisted of primary, secondary, and tertiary sources, which were analyzed qualitatively to identify applicable legal norms and accountability mechanisms. The findings indicate that maladministration in mining licensing may take several forms, including abuse of authority, procedural deviations, prolonged delays, neglect of legal obligations, and conflicts of interest. These practices may create legal uncertainty, social harm, environmental damage, and potential financial losses to the state. In legal terms, such maladministration may give rise to administrative, civil, and criminal liability, depending on the nature of the violation and its consequences. Administrative responsibility may result in sanctions, cancellation of decisions, or revocation of permits; civil responsibility may involve compensation for harmed parties; and criminal responsibility may apply when the act fulfills the elements of corruption or abuse of authority. The study also shows that oversight institutions, particularly the Ombudsman and administrative courts, play a vital role in preventing and addressing maladministration in the mining permit process. Strengthening these accountability mechanisms is essential to ensure good governance, legal certainty, and protection of the public interest in the management of mineral and coal resources.